Earth politics and intangible heritage : three case studies in the Americas - Christie, Jessica Joyce, 1956- (Cultural heritage studies., 2021)
"Focusing on three communities in the Americas, this book layers archaeological research with oral narratives and social memories, demonstrating a way of reconciling the tension between Western scientific and local Indigenous approaches to history"--